Structural-semantic and etnokulturogycal characteristics of the somatisms (for example phrasems with component eye) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
The article highlights the issue of the functioning of phrasems with somatic component in the language picture of the world and justifies the factors that affect on their formation. Reviewed the structural-semantic and etnokulturology characteristics of the phrasems with somatic component (for example phrasems with component eye), analyzed the main trends of modern linguistic studies, traced the development of future research etnokulturology phrasems with somatic component.
Keywords: phraseology; phraseological units; phraseme; somatism; language picture of the world